Rodziny liturgiczne chrześcijańskiego Wschodu – panorama - Potoczny, Mateusz (Teologia i Człowiek, 2014)
The life of the Eastern Churches and their liturgies still remain a deep well of undiscovered riches for many, their fertile and varied traditions are signposts indicating ways of being authentically Christian and truly catholic – in the full universal sense of that word. The return ad fontes liturgicos, called for by the Second Vatican Council, drew deeply from the wisdom of the ancient Churches, which were born – as indeed was the whole of Christianity – “in the East”; the research that was to follow, based on this essential insight, allowed many to reach that desired goal. That sense of dealing with the seamless and undivided garment of the tradition of the whole Church, allowed a complete picture of Christianity to emerge and be presented. The knowledge gained from this research also enabled us to find both an appropriate self understanding for the Christian today and a fuller sense of our Christian faith which draws deeply from its rich and ancient traditions. In this paper the author has tried to give an outline of Eastern Christianity, firstly the geographical setting and historical foundation of the East/Orient and secondly the oriental meaning and understanding of their use of the term “rite”. Such a study allows for a fuller understanding of the two Eastern liturgical families (derived from Antioch and Alexandria) and the seven different traditions which flow from them. The general outline given here will hopefully enable a given Polish reader, unfamiliar with this subject, the ability to see the dimensions of the rich liturgical treasure of the Oriental Churches.